2012
DOI: 10.1177/1941738112461621
|View full text |Cite
|
Sign up to set email alerts
|

Sports Health Benefits of Vitamin D

Abstract: Context:Vitamin D is a potent secosteroid hormone that provides many skeletal and extraskeletal health benefits. Musculoskeletal injury prevention and recovery are potentially affected by sufficient circulating levels of the storage form of vitamin D: 25-hydroxyvitamin D3, or 25(OH)D. Vitamin D deficiency can exist among young, active, and healthy people, which may put them at increased risk for injury and prolonged recovery.Evidence Aquisition:PubMed was searched using vitamin D and skeletal muscle, vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 70 publications
1
97
0
7
Order By: Relevance
“…10 Vitamin D signaling has additionally been reported to alter the expression of myotubular sizes, indicating a direct positive effect on the contractile filaments and thus muscle strength, while it prevents muscular degeneration and reverses myalgia. 11,12 Last but not least, vitamin D accelerates muscle recovery from the stress of intense exercise.…”
Section: Effects Of Vitamin D On Skeletal Musclesmentioning
confidence: 99%
“…10 Vitamin D signaling has additionally been reported to alter the expression of myotubular sizes, indicating a direct positive effect on the contractile filaments and thus muscle strength, while it prevents muscular degeneration and reverses myalgia. 11,12 Last but not least, vitamin D accelerates muscle recovery from the stress of intense exercise.…”
Section: Effects Of Vitamin D On Skeletal Musclesmentioning
confidence: 99%
“…11 Walking exercise increases the level of vitamin D3 > 30 min daily. 12 About drug history RA patient's treatment are (DEMARD alone, combined DEMARDs or DEMARD + Biological agent). 13,14 The activity of disease was assessed by DAS28 and CDAI parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It's also a hormone in the same way as growth hormone is a hormone. Activated vitamin D (calcitriol) is a steroid hormone, which regulates more than 1000 vitamin D-responsive human genes, may influence athletic performance [7,53,36]. Recent research indicates that these genes affect muscle protein synthesis, muscle strength, muscle size, reaction time, balance, coordination, endurance, inflammation, and immunity-all are important to maintain sports health and athletic performance.…”
Section: Vitamin D and Athletic Performancementioning
confidence: 99%
“…Vitamin D deficiency is recognized as a worldwide epidemic, athletes are no exception. Several studies have focused a high prevalence of vitamin D insufficiency and deficiency in the general population worldwide, whereas only few studies have found on athletes [30,52,53,59]. Vitamin D deficiency produces muscle fiber atrophy, slow peak muscle contraction; prolonged time to muscle relaxation, and increased risk of chronic musculoskeletal pain associated with different sports persons.…”
Section: Vitamin D and Athletic Performancementioning
confidence: 99%